Knowledge Sharing Networks Used by Academicians in Malaysian Public University (Sains Humanika, 2014)
This qualitative study aims to explore and describe the knowledge sharing networks used by academicians to share their knowledge. The study was conducted in a Malaysian public university. A single case study strategy used to gather deeper insights on the knowledge sharing networks. A face-to-face semi-structured interview was conducted to collect the data over a six month period. A total of 15 renowned academicians were interviewed. Content analysis method was used to extract the knowledge sharing categories from the qualitative data. The study reveals that academicians share their knowledge through three main knowledge sharing networks, namely Business Club network, Research network, and Personal network. The research findings may expand a research area of knowledge sharing networks in universities which still theoretically and empirically not sufficiently covered.Â
Keywords: Knowledge sharing network; academicians; malaysian public academic institutions